Relationship between subjective socioeconomic status and sense of gain of health-care reform and the mediating role of self-rated health: a cross-sectional study in China - SU Yuan; LI Yueping (BMC, 2022)
Abstract Background The sense of gain has gradually become the main evaluation index for the effectiveness of China's deepening reform and is affected by many factors. However, there is no relevant research on the sense of gain of health-care reform (SGHR) and its influencing factors. The purpose of this study was to explore the influence of subjective socioeconomic status (SSS) on SGHR and the mediating role of self-rated health (SRH) between them. Methods Data (25,149 samples total) from China Family Panel Studies (CFPS) in 2018 were included in the analysis. A nonparametric test was used to explore the differences in demographic characteristics of SGHR, and a correlation analysis and mediating effect model were used to explore the influence of SSS on SGHR and the mediating effect of SRH. Results Demographic characteristics such as age, urban and rural areas, educational background, marriage and choice of medical treatment had significant differences in the distribution of perceived acquisition of medical reform. SSS, SRH and SGHR are statistically positively correlated with each other. SSS has a positive statistical correlation with SGHR, and may have an indirect effect through SRH. Conclusions SSS is an important predictor of SGHR, and SRH may play a partially mediating role in SGHR.